2015
DOI: 10.4238/2015.august.14.5
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification and analysis of phytoene synthase genes in plants

Abstract: ABSTRACT. In this study, we examined phytoene synthetase (PSY), the first key limiting enzyme in the synthesis of carotenoids and catalyzing the formation of geranylgeranyl pyrophosphate in terpenoid biosynthesis. We used known amino acid sequences of the PSY gene in tomato plants to conduct a genome-wide search and identify putative candidates in 34 sequenced plants. A total of 101 homologous genes were identified. Phylogenetic analysis revealed that PSY evolved independently in algae as well as monocotyledon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The PSY proteins used in this study have a wide range of pI values from 5. inter-domain similarity concerning pI values which is similar to previous reports of plant origin phytoene synthases showing a wide range of pI values (Iwata-Reuyl et al 2003;Lao et al 2011;Han et al 2015).…”
Section: Isoelectric Point (Pi)supporting
confidence: 89%
“…The PSY proteins used in this study have a wide range of pI values from 5. inter-domain similarity concerning pI values which is similar to previous reports of plant origin phytoene synthases showing a wide range of pI values (Iwata-Reuyl et al 2003;Lao et al 2011;Han et al 2015).…”
Section: Isoelectric Point (Pi)supporting
confidence: 89%
“…Bioinformatics analysis can play a vital role in the interpretation of proteomic data. These methodologies have been extensively used for predicting function and structure of proteins from its amino acid sequences 24,27,28,52,53,55 . The identification of the characteristics of these proteins during parasitism can serve as an important tool in the construction of control strategies for root-knot nematodes and its interactions with their host plants.…”
Section: Discussionmentioning
confidence: 99%
“…This type of experimentation represents a low cost alternative for studies on biological functions with very precise computational models when compared with laboratory conditions. Computational analyzes have been used in the characterization of several proteins and enzymes in both eukaryotes and prokaryotes, in search of genes linked to parasitism and resistance in host species [25][26][27][28][29][30][31] . The identification of proteins involved in the relationship of parasitism of nematodes and plants can provide important tools for research that develop plant species with resistant genes and in the search for mechanisms that avoid the breakdown of this resistance by phytonematodes.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have identified a number of genes including WRKY genes, Ascorbate Peroxidase, PSY, etc. using different bioinformatics tools [38][39][40].…”
Section: Analysis Of Regulatory Elementsmentioning
confidence: 99%